Knowledge, Attitudes, and Practices of Postoperative Pain Management by Nurses in Selected District Hospitals in Ghana - Awube Menlah MN; Isabella Garti MN; Sarah Ama Amoo MN; Confidence Alorse Atakro MN; Caleb Amponsah BSc; Dorcas Frempomaa Agyare MN (SAGE Publishing, 2018)
Introduction There is documented evidence pointing to the fact that there are numerous challenges with postoperative pain (POP) management globally. However, these challenges with POP management are more profound in developing countries. Purpose The purpose of this study is to examine the knowledge, attitude, and practices of nurses concerning POP management in four selected district hospitals in Ghana. Methodology A descriptive, cross-sectional survey was employed to evaluate nurse's knowledge, attitude, and practices pertaining to POP management. Multistaged sampling was used to draw the respondents. An adapted version of the Nurses Knowledge and Attitudes Survey Regarding Pain instrument was used to test the knowledge, attitude, and practices of nurses and midwives. Descriptive statistics were used to analyze the data in order to present quantitative descriptions of variables in this study. Results This study showed that nurses in the four district hospitals had knowledge deficits regarding POP management. Eighty-one representing 48% of nurses had low knowledge on POP management. An overwhelming majority of nurses (97.6%) relied on routinely rendered basic nursing skills to relieve POP and a few used pharmacological interventions. However, nurses had good attitudes toward POP management. Conclusions POP is ineffectively managed by nurses in district hospitals in Ghana. Nurses and midwives in Ghana need to adhere to best practices in POP management by increasing their theoretical and practical knowledge, so that there will be tangible positive change in POP management in Ghana. Recommendations Nurses must be empowered through continuous development programs to keep abreast with changing trends that pertain to POP management.